A Religious Leaders' Perceptions Of The Practice Of Nikah Siri To Avoid Marriage Dispensation In Nanggung - Al Musapaah , Siti Pariqoh; Yono; Hamdani, Ikhwan (IBN KHALDUN BOGOR, 2025)
In Indonesia, marriage is regulated by Law No. 1/1974 on Marriage, which governs all aspects of marriage for all citizens, including Muslims. One of the provisions in the law is the minimum age of marriage, where couples who have not reached it are required to apply for marriage dispensation to the Religious Court. However, in practice, some people choose the siri marriage route as an alternative to avoid the marriage dispensation procedure. The main reason is that the procedure is considered complicated, time-consuming, and potentially socially stigmatizing. This study aims to find out the perceptions of religious leaders in Nanggung Sub-district, Bogor Regency, towards the practice of siri marriage to avoid marriage dispensation, and to identify the factors that encourage people to make this choice. This research used a qualitative approach with a case study method. Data collection techniques included in-depth interviews, observation, and documentation. The research was conducted in Nanggung Sub-district, Bogor Regency. The results showed that religious leaders have diverse views on the practice of nikah siri, ranging from excusing it due to social conditions to criticizing its legal impact. The factors driving people to choose nikah siri include legal and regulatory reasons, socio-cultural conditions, economic pressures, and limited access to formal institutions. Although considered a practical solution, this practice has severe negative impacts, such as the absence of legal proof of marriage, unclear legal status of children, and the lack of legal protection for wives, which in turn reinforces the culture of avoiding official legal channels. Keywords: Religious Leaders; Siri Marriage; Marriage Dispensation